Water engineering in the ancient world: archaeological and climate perspectives on societies of ancient South America, the Middle East, and South-East Asia - Ortloff, Charles R. (Oxford University Press, 2009)
Ancient pre-Columbian Peru, Bolivia and Mesoamerica -- The ancient Middle East -- Ancient South-East Asia -- Hydraulic engineering and water management strategies of ancient societies -- Environmental and climate perspectives on New World, Old World, and South-East Asian societies' achievements in the hydraulic sciences